2020
DOI: 10.13106/jafeb.2020.vol7.no8.509
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Government Regulations in Enhancing Corporate Social Responsibility Disclosure and Firm Value

Abstract: This study investigates, first, whether the extent of corporate social and environmental responsibility disclosure (CSERD) differs between 2010 and 2014; second, whether government regulation affects the extent of CSERD; and, third, whether the CSERD is valued by investors. Content analysis method was used to extract 466 companies' annual reports to measure the extent of social and environmental responsibility disclosure based on the Global Reporting Initiative (GRI) checklist. Independent sample t-test and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 56 publications
0
40
0
3
Order By: Relevance
“…Most CSR literature mentions that shareholders, employees, suppliers, society, and investors are the main stakeholders of companies (Gunawan, 2010). Studies found that governments are especially powerful in developing countries (Dieleman & Widjaja, 2018), and pressure from the government can significantly impact corporate disclosure (Faisal, Situmorang, Achmad, & Prastiwi, 2020;Nguyen, Nguyen, Nguyen, Le, & Nguyen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Most CSR literature mentions that shareholders, employees, suppliers, society, and investors are the main stakeholders of companies (Gunawan, 2010). Studies found that governments are especially powerful in developing countries (Dieleman & Widjaja, 2018), and pressure from the government can significantly impact corporate disclosure (Faisal, Situmorang, Achmad, & Prastiwi, 2020;Nguyen, Nguyen, Nguyen, Le, & Nguyen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the existence of government regulation can increase disclosure, especially the various voluntary disclosure initiatives are unlikely to succeed if there is no pressure from the government in the form of binding regulations. The company seeks to comply with government regulations to maintain its viability and to build a good reputation in the community (Faisal et al, 2020). In line with previous studies, we formulate the following hypothesis: H1: The more rigorous state governance is, the higher the level of information transparency achieved.…”
Section: State Governance In Information Transparencymentioning
confidence: 78%
“…The awareness of developed countries such as Japan and South Korea about sustainability is becoming higher because it is supported by the availability of resources such that it affects the increase in firm value. Overall, both developed and developing countries in Asia show an increase in firm value due to sustainability (Faisal et al, 2020;Laskar, 2018;Laskar & Maji, 2018). Conditions in Nigeria indicate the same thing, that better sustainability practices can improve firm performance (Dembo, 2017).…”
Section: H 2 : the Acgs Has A Positive Effect On Firm Valuementioning
confidence: 97%